Death due to homicidal firearm injury and concealment of crime: A case series - Vinod Kumar; Tarun Dagar; Jai Prakash Soni; Chander Bhan (Asian Journal of Medical Sciences, 2025)
A firearm is a dangerous weapon used by a person in self-defense and to kill another person because of various reasons. It is also used by the defense personnel for the safety and security of citizens of a country and other reasons. Unlicensed firearm weapons are used by many persons with ill intentions, such as robbery, threat, kidnapping, and murder. Injuries due to firearm weapons can be homicidal, suicidal, and accidental. In many cases, a person is killed by the assailant by firearm weapon, and then the body is disposed of at various places to conceal the crime. In the present case series, the authors present three cases of death due to firearm injuries where the disposal of the body by the assailant was done at different places to conceal the crime. However, on meticulous postmortem examination of the deceased, exact cause of death, manner of death, nature of injury (antemortem/postmortem), type of weapon, and time since death was opined helps the investigating agency to solve the crime and delivery of justice to the family of the victim.